2021
DOI: 10.5755/j02.mech.27815
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of The Cycloidal Drive Sleeves and Pins

Abstract: In the paper, an issue of CMM measurement strategy of the sleeves and pins designed for wear tests in the cycloidal drive. The measurement strategy was proposed, based on initial out-of-roundness measurement in scanning mode. Proposed approach ensured that the pin was measured along its entire 40 mm length with only small area of fixation ca. 5 mm left out, and all probing points for cylindricity deviation assessment were collected in one fixation. It was demonstrated that the cylindricity and roundness measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…In their article [9], R. Zareba, T. Mazur, et al assert that a comparison of different drives revealed the superior efficiency of two-stage cycloidal drives, which achieved a remarkable efficiency of 92.7%. This high efficiency was considered advantageous.…”
Section: Overview Of the Papers Published In The Field Of The Issue A...mentioning
confidence: 99%
“…In their article [9], R. Zareba, T. Mazur, et al assert that a comparison of different drives revealed the superior efficiency of two-stage cycloidal drives, which achieved a remarkable efficiency of 92.7%. This high efficiency was considered advantageous.…”
Section: Overview Of the Papers Published In The Field Of The Issue A...mentioning
confidence: 99%
“…Studies in the field of cycloidal gearbox engineering deal with the subject of design issues [7][8][9][10][11][12][13], finite element analysis of the cycloidal gearbox parts [7,[13][14][15][16][17], kinematical analysis [16,18], applications in robotics [12,16,17,19], friction, lubrication and machining [20][21][22][23][24], measurements [25], efficiency [26,27], optimisation [8,28], contact modelling [29][30][31][32], backlash and design tolerances [9,30,[33][34][35] or vibration and dynamics [31,32,[36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%